Cardiotoxicity from anthracycline and cardioprotection in paediatric cancer patients. (May 2016) - Bassareo, Pier P.; Monte, Ines; Romano, Claudia; Deidda, Martino; Piras, Alessandra; Cugusi, Lucia; Coppola, Carmela; Galletta, Francesca; Mercuro, Giuseppe
Abstract : Notwithstanding the steady progress in survival rates of children and adolescents suffering from cancer, the benefits associated with chemotherapy do not come without risks involving multiple organs and systems, including the cardiovascular apparatus. Anthracyclines—often administered in combination with radiation therapy and/or surgery—are the most used chemotherapeutic compounds in order to treat tumours and blood malignancies even in paediatric age. Being an important side-effect of anthracyclines, carduitoxicity may limit their efficacy during the treatment and induce long-term sequelae, observed even many years after therapy completion. The purpose of this review was to perform an overview about all the possible strategies to prevent and/or limit the anthracyclines adverse side-effects for the cardiovascular system in childhood cancer survivors.